Comparison of prognosis for T4b rectal cancer with different pelvic compartment involvement treated using neoadjuvant chemoradiotherapy and implications for refinement of the current T staging system: A retrospective cohort study - Yang-zi Zhang; Maxiaowei Song; Shuai Li; Jian Tie; Xiang-gao Zhu; Yong-heng Li; Ai-wen Wu; Yong Cai; Wei-hu Wang (Translational Oncology)
Purpose: Although classified as one stage, T4b rectal cancer actually represents a group of heterogeneous diseases. Our study aimed to assess the prognosis difference of T4b rectal cancer involving inferior pelvic and other pelvic compartments. This information may be helpful in refinement of the current T staging system. Methods: We retrospectively analysed data from 195 patients with magnetic resonance imaging-identified locally advanced T4b rectal cancer who received neoadjuvant chemoradiotherapy between January 2010 and December 2019. 104 patients had only inferior pelvic compartment involvement (group A) while 91 patients had anterior, posterior or lateral pelvic compartment involvement (group B). Short-term and long-term outcomes were compared between the two groups. Results: After neoadjuvant therapy, 80.8 % patients (84/104) in group A and 92.3 % patients (84/91) in group B underwent surgery. The R0 resection rates were 97.6 % and 89.3 %, respectively. 8.7 % patients (9/104) in group A achieved clinical complete response and adopted watch-and-wait strategy. Patients in group A had significantly superior 5-year progression-free survival (PFS) (67.8 % vs. 55.5 %, P = 0.032) and overall survival (OS) (89.6 % vs. 71.8 %, P = 0.001) than group B. Multivariable Cox regression analysis also identified pelvic compartment involvement classification as an independent predictor of PFS (hazard ratio 1.776, P = 0.046) and OS (hazard ratio 3.477, P = 0.004). Conclusion: T4b rectal cancers with involvement limited to the inferior pelvic compartment had superior prognosis compared to those involving other pelvic compartments. These differences should be investigated further and taken into consideration in refinement of the current T staging system.